Relationship between bedtime, nighttime sleep duration, and anxiety symptoms in preschoolers in China - Qiu, Shuang-Yan; Yin, Xiao-Na; Yang, Yanni; Li, Ting; Lu, Dali; Li, Jie-Min; Yang, Wei-Kang; Wen, Guo-Ming; Zhang, Jing-Yu; Zhang, Yan; Lei, Hai-Yan; Wang, Xin; et al. (Frontiers in Psychology, 2024)
Sleep problems in preschoolers are becoming increasingly prominent, and the association between sleep status and anxiety symptoms has attracted growing attention. However, studies investigating the relationship between bedtime and nighttime sleep duration in preschoolers and their anxiety symptoms remain scant. We used the large sample data from the Longhua Cohort Study of Children in Shenzhen, China (LCCS) to analyze the association between bedtime and sleep in preschoolers and their anxiety symptoms.A cross-sectional study of 69,138 preschoolers in Longhua District, Shenzhen, China was conducted in 2022. Data on sociodemographic characteristics of families, bedtime, nighttime sleep duration of preschoolers, and their anxiety symptoms (measured by the Spence Preschool Children Anxiety Scale) were collected through a structured questionnaire completed by the parents. Using binary logistic regression models, the relationship between bedtime, nighttime sleep duration, and childhood anxiety symptoms was examined.